The effect of Benson relaxation application (‘Bens app’) on reducing fatigue in patients with breast cancer undergoing chemotherapy: A quasi-experimental study - Hendra Dwi Cahyono; Dewi Irawaty; Muhamad Adam (Belitung Raya Foundation, Indonesia, 2022)
Background: Fatigue is the most common symptom in patients with breast cancer undergoing chemotherapy. Benson’s relaxation technique is considered effective to reduce fatigue, but its effect in combination with smartphone technology is limited. Objective: This study aimed to analyze and determine the effect of the Benson relaxation application (Bens app) on fatigue in patients with breast cancer undergoing chemotherapy. Methods: A quasi-experimental design with a pretest-posttest comparison group was used. Fifty-six patients were included using consecutive sampling technique, of which 28 were assigned to the experimental group (received Benson relaxation technique using Bens app) and comparison group (obtained Benson relaxation technique using booklet). The Benson relaxation was done two times per day for seven days, and the Brief Fatigue Inventory questionnaire was used to measure the patients’ fatigue levels. Data were analyzed using paired and independent t-tests. Results: The experimental group (p = 0.001) and the comparison group (p = 0.015) showed a significant reduction in fatigue after receiving the Benson relaxation for seven days. However, there was a statistically significant difference in fatigue between the experiment and comparison groups after the intervention (t55 = 2.481, p = 0.016). Conclusion: Benson relaxation could reduce fatigue in patients with breast cancer using the Bens app and booklet. However, the Bens app is considered more effective than a booklet. Therefore, the Bens app can be viewed as an alternative to help patients perform Benson relaxation and integrated into the nurse palliative care program for patients with cancer.